The role of management coaching in employee engagement in an organisational change process in South Africa - Rukande, Marilyn (My University, 2021)
Organisations need to have actively engaged managers, who can deliver performance and lead change to thrive in uncertain, ever-changing business environments. The current research study explored the lived experiences of first line managers, their experiences of change, and strategies of managing change, the influence coaching had on their engagement, and ability to lead change. Management coaching was conducted using the Solution-Focused Cognitive Behavioural (SFCB) coaching approach as the underpinning theory for driving leadership engagement in organisational change. A qualitative research approach with purposive sampling, pre-and post-coaching assessment, the SFCB approach using the PRACTICE-model was conducted. The data collection was conducted using semi-structured interviews of participants and analysed using thematic data analysis to determine the themes from the participants' experiences. It was found that Management Coaching rekindled the participants' passion for their jobs, making them look forward to going to work. The engagement of managers enhanced authenticity, teamwork, leading by example, proactive behaviours, communication, and the buy-in for managing change. Role clarity, involvement, empowerment, and motivation were mentioned as drivers of engagement, and the strategies for managing change included the importance of having the mindset to focus on what is in your control and the importance of wellbeing when remote working. The findings revealed the contributions management coaching had on creating and sustaining managers' engagement to manage change effectively, providing empirical evidence to literature. Managers’ engagement positively influenced their ability to lead change, and the drivers of engagement need to be promoted to ensure coaching interventions enhance engagement.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Management coaching; Employee engagement; Organisational change; UCTD; SDG-8: Decent work and economic growth